Respuestas

  • Usuario de Brainly
2013-08-13T17:45:51+02:00
Aqui esta
Suma de Polinomios:
P(x) = 2x3 + 5x - 3 Q(x) = 2x3 - 3x2 + 4x

P(x) + Q(x) = (2x3 + 5x - 3) + (2x3 -3x2 + 4x) 

P(x) + Q(x) = 2x3 + 2x3 - 3 x2 + 5x + 4x - 3

P(x) + Q(x) = 4x3- 3x2 + 9x - 3.

Resta de Polinomios:
P(x) − Q(x) = (2x3 + 5x - 3) − (2x3 - 3x2 + 4x) 

P(x) − Q(x) = 2x3 + 5x - 3 − 2x3 + 3x2 − 4x

P(x) − Q(x) = 2x3 − 2x3 + 3x2 + 5x− 4x - 3

P(x) − Q(x) = 3x2 + x - 3

Multiplicación de Polinomios:
P(x) = 2x2 - 3 Q(x) = 2x3 - 3x2 + 4x

P(x) · Q(x) = (2x2 - 3) · (2x3 - 3x2 + 4x) =

4x5 − 6x4 + 8x3 − 6x3 + 9x2 − 12x = 

4x5 − 6x4 + 2x3 + 9x2 − 12x 
2013-08-13T17:53:39+02:00